An Experimental Comparison of Traditional and ChatGPT Assisted Writing Instruction: Effects on EFL Learners’ Writing Performance - Raziyeh Afra; Venus Jalali (Universitas Uluwiyah Mojokerto, Indonesia., 2025)
The integration of artificial intelligence (AI) into teacher education is rapidly transforming reflective practice by offering scalable, personalized tools to support professional learning. Reflective journaling, a core activity in teacher preparation, can be enhanced through AI-driven platforms that provide real-time feedback, adaptive prompts, and metacognitive scaffolding. This study examined the impact of AI-powered reflective journals on reflective thinking, instructional self-efficacy, and pedagogical adaptability among pre-service teachers. A sequential explanatory mixed-methods design was employed with 80 male Iranian pre-service teachers, randomly assigned to an experimental group (n = 40) and a control group (n = 40). Over a 10-week intervention, the experimental group engaged in structured AI-supported journaling, while the control group maintained traditional, unstructured pen-and-paper journals. Pre- and post-test data were collected using validated instruments measuring the three targeted constructs. Independent samples t-tests confirmed group equivalency at baseline. ANCOVA results revealed statistically significant post-intervention improvements in the experimental group for reflective thinking (F = 10.49, p < .001, η² = .12), instructional self-efficacy (F = 14.38, p < .001, η² = .16), and pedagogical adaptability. Thematic analysis of semi-structured interviews supported the quantitative findings, with participants reporting that AI-generated feedback facilitated deeper self-reflection, strengthened instructional confidence, and fostered adaptability to diverse learner needs. These findings highlight the potential of AI-mediated reflective tools to enhance core professional competencies in teacher education.